The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1128/jvi.77.20.11260-11267.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of the Psittacid Herpesviruses Causing Pacheco's Disease: Correlation of Genotype with Phenotypic Expression

Abstract: Fragments of 419 bp of the UL16 open reading frame from 73 psittacid herpesviruses (PsHVs) from the United States and Europe were sequenced. All viruses caused Pacheco's disease, and serotypes of the European isolates were known. A phylogenetic tree derived from these sequences demonstrated that the PsHVs that cause Pacheco's disease comprised four major genotypes, with each genotype including between two and four variants. With the exception of two viruses, the serotypes of the virus isolates could be predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 14 publications
2
33
0
Order By: Relevance
“…In the picornavirus, for example, structural genes cluster according to viral serotypes (Simmonds, 2006). Similarly, in psittacid herpesviruses, the serotypes of the virus isolates could be predicted by their genotypes (Tomaszewski et al, 2003). For bovine pestivirus, it has been shown that strains belonging to different genotypes lead to altered clinical manifestations in infected cattle (Baule et al, 1997(Baule et al, , 2001Jones et al, 2001), which resulted in the proposal that the diversification of this virus could be driven by viral adaptation in order to use multiple different pathogenic strategies (Jones et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the picornavirus, for example, structural genes cluster according to viral serotypes (Simmonds, 2006). Similarly, in psittacid herpesviruses, the serotypes of the virus isolates could be predicted by their genotypes (Tomaszewski et al, 2003). For bovine pestivirus, it has been shown that strains belonging to different genotypes lead to altered clinical manifestations in infected cattle (Baule et al, 1997(Baule et al, , 2001Jones et al, 2001), which resulted in the proposal that the diversification of this virus could be driven by viral adaptation in order to use multiple different pathogenic strategies (Jones et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The later interpretation appears to be more likely. PsHV-1 genotype 2 was found in 4 parrots submitted for necropsy and 3 parrots from the Schubot collection 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Genotypes 1, 2, and 3 correspond respectively to serotypes 1, 2, and 3, while genotype 4 is also serotype 1 3,14 . Multiple birds in this study were found to be coinfected with two PsHV-1 genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations